Unveiling the “common soil” of cardiovascular disease and cancer - Licia Iacoviello; Maria Benedetta Donati (Bleeding, Thrombosis and Vascular Biology)
The complex relationship between cardiovascular disease (CVD) and cancer has raised significant research interest, supported by growing evidence that these leading causes of morbidity and mortality share several pathogenetic aspects. The “common soil“ hypothesis postulates that CVD and cancer emerge from the same piece of earth as distinct trees, but with intermingled roots, represented by modifiable risk factors and underlying molecular mechanisms. The integration of cardiovascular and cancer prevention through lifestyle and metabolic health improvements represents a necessity, for modern public health. This dual-benefit approach has the potential to reshape how we understand, approach, and ultimately reduce the burden of two of the world's most impactful group of diseases.